Stress exposure and psychological stress responses are related to glucose concentrations during pregnancy. Issue 3 (12th May 2016) - Horsch, Antje; Kang, Ji Seon; Vial, Yvan; Ehlert, Ulrike; Borghini, Ayala; Marques‐Vidal, Pedro; Jacobs, Ingo; Puder, Jardena J.
Abstract : Objectives: The role of stress in the development of gestational diabetes mellitus (GDM) has so far been neglected. We investigated the impact of stress exposure (pregnancy‐related and pregnancy‐unrelated major life events), psychological stress responses (perceived stress, subjective experience of stress, anxiety, depression, sleep), and physiological stress responses (salivary cortisol, plasma copeptin levels) on glucose concentrations during pregnancy. Design: Cross‐sectional study, including 203 pregnant women at the maternity department of a Swiss university hospital. Methods: All women underwent routine screening for GDM with a 75‐g oral glucose‐tolerance test at 24–30 weeks of gestation. Pregnancy‐related and pregnancy‐unrelated major life events, perceived stress, general psychological distress, anxiety, depression, and amount of sleep were assessed by validated self‐report questionnaires. Cortisol was measured using fasting and bedtime saliva samples, and copeptin using fasting plasma. All data were collected before communication of the screening test results. Results: Significant positive associations were found between the number of pregnancy‐related major life events and fasting glucose, while there was no association with pregnancy‐unrelated major life events. More anxiety and depressive symptoms, a higher general level of distress, and a shorter duration of sleep were related to fasting glucose, although the latter two were no longer significant when age and BMI were controlled for. However, physiological stress responses were not associated with glucose concentrations. When testing for unique associations with fasting glucose, more general distress and shorter duration of sleep independently accounted for higher fasting glucose levels. Finally, when comparing women with and without GDM, we found that women who subsequently received the diagnosis of GDM reported more pregnancy‐related life events. Conclusions: Some indicators of stress exposure and psychological stress responses were associated with fasting glucose concentrations in pregnant women, thus representing important risk factors for GDM development. Statement of contribution What is already known on this subject? Only approximately half of women with gestational diabetes mellitus (GDM) report any known risk factors. Women after GDM diagnosis reported more major life events compared to healthy pregnant controls. What does this study add? Stress exposure and psychological stress responses were associated with fasting glucose concentrations in pregnant before women were aware of their GDM diagnosis. These represent important risk factors for GDM development and potential targets for intervention.